Overwhelmed by overflows? How people and organizations create and manage excess - Barbara Czarniawska; Orvar Löfgren (Lund University Press, 2019)
This book presents studies of ways in which people and organizations deal with the overflow of information, goods, or choices. The contributors explore two main themes. The first is the emergence of overflows: What is defined as overflow? Here the notion of framing as coined by Michel Callon has guided our approach. There is no overflow until some flow has been framed; framing means defining, and defining means imposing borders. Who does it, how, and why? The answer to these questions necessitates an historical and comparative approach. What one culture defines as necessity, another may see as excess, and these differences can exist even between different levels of the same social hierarchy. The second theme is the management of overflows, in the double meaning of the term: as controlling and as coping. Coping with overflow means learning to live with it; controlling overflow requires various skills and devices. The individual chapters show the management of overflow taking place in various social settings, periods, and political contexts: From the attempts of states to manage future consumption overflow in post-war Eastern European to the contemporary economies of sharing. Other contributions focus on overflow in healthcare administration, overflow problems in mass travel and migration, overflow in digital services, and the overflow that scholars face in dealing with an abundance of research information and publications. This edited volume belongs to the transdisciplinary social sciences, and therefore it should be of interest to sociologists, management scholars, economists, historians, anthropologists, and cultural studies scholars.
Keywords: 320; overflow; framing; abundance; excess; management; Konsumgesellschaft; Wissensgesellschaft; Postindustrielle Gesellschaft; Arbeitsgesellschaft; Wirtschaftsordnung; Wirtschaftssoziologie